Strategies for Managing Facilities and Infrastructure in Inclusive Schools - Santi, Arina; Komariah, Laili; Mulawarman , Widyatmike Gede; Nurlaili; Akhmad; Azainil (Research Horizon, 2025)
Inclusive education aims to provide access to quality education for all children, including children with special needs. Implementation in Indonesia still faces various challenges, especially in the management of disability friendly facilities and infrastructure. This study aims to explore the management of inclusive education facilities and infrastructure. This study uses a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation for five months (August–December 2024). School has provided inclusive education facilities, such as accessible classrooms, disability-friendly toilets, ramps, and Disability Service Units. However, there are still limitations in special learning aids. Management of facilities and infrastructure is carried out through annual planning, routine monitoring, and periodic evaluation, not yet supported by special experts in inclusive services. The main challenges faced are budget constraints and lack of professional human resources. This study emphasizes the importance of adaptive and planned management of facilities and infrastructure in creating an inclusive learning environment. School has implemented strategies by applying for assistance to the Education Office, collaborating with community organizations, and holding inclusive education training for teachers. These findings can be a reference for schools in improving the effectiveness of inclusive education facility management.